Fabrication of multilayer electronic magnetic window material by Si2N2O decomposition. (5th May 2016) - Lin, Shaojie; Ye, Feng; Ma, Jie; Ding, Junjie; Yang, Chunping; Dong, Shangli
Abstract: Silicon oxynitride (Si2 N2 O) based wave transparent material with multilayer structures was fabricated by a two step sintering route. Influences of temperature and atmosphere on microstructure and properties of the materials were investigated. Results showed that the decomposition of Si2 N2 O is the reason of such multilayer structure. Thickness of the β-Si3 N4 outer layers and the Si2 N2 O inner layer could be tailored by adjusting the decomposing temperature. The flexural strength of the material was decreased after decomposed at 1600 °C–1700 °C, while decomposition occurred at 1800 °C strengthened the ceramic bodies. Materials with such structures showed good mechanical properties (flexural strength δ = 210–236 MPa) and suitable dielectric properties (dielectric constant ε < 4.8, loss tangent tanδ < 0.0044). This simple process allows the gas pressure sintered Si3 N4 /Si2 N2 O/Si3 N4 ceramic composites to be widely used as the radome material for military and commercial applications. Graphical abstract: The decomposition of Si2 N2 O is the reason for the formation such multi-layer structure. The outer layers are β-Si3 N4, while the inner layer is Si2 N2 O. Highlights: Two types of sandwich structures were obtained by adjusting the Si2 N2 O decomposition. Outer layers were pure β-Si3 N4, while the inner layer is Si2 N2 O. Layer thickness is tunable by controlling the decomposition temperature. The mechanical and dielectric properties can be tailored.